A multifunctional cadmium–organic framework comprising tricarboxytriphenyl amine: selective gas adsorption, liquid-phase separation and luminescence sensing12. Issue 2 (23rd December 2015) - Wen, Lili; Wang, Xiangfang; Shi, Hui; Lv, Kangle; Wang, Chenggang
Abstract : A multifunctional cadmium–organic framework demonstrates impressive adsorption enthalpies for CO2 and H2, and possesses the second adsorption capacity for MO among the MOFs as well as displays strong guest-dependent luminescence. Abstract : The reaction of tricarboxytriphenyl amine (H3 TCA) with Cd II and auxiliary ligand 4, 4′-bis(1-imidazolyl)biphenyl (bimb) afforded [Cd3 (TCA)2 (bimb)·(DMA)6 ] n (1 ) containing a two-fold interpenetrating three-dimensional microporous framework. Compound1 showed remarkable adsorption enthalpies for CO2 and H2 and good H2 /N2 selectivity at low temperature. Moreover, activated1 showed a highly selective adsorption towards CO2 over N2 and CH4 under ambient conditions. Interestingly, compound1 selectively removed methyl orange (MO) over methylene blue (MB) from contaminated water with good recyclability, and possessed the second highest adsorption capacity for MO among the MOFs reported to date. Remarkably, complex1 showed strong guest-dependent luminescence behavior.